From Page to Stage, Linguistic to Multimodal: Stage Adaptations from Literary Texts - Sağlam, Naciye (My University, 2022)
Roman Jakobson's three-fold classification of translation is recognized as a turning point in translation studies. Though its legacy endures, in the present day it becomes necessary to reconsider this classification due to the evolving definition of the text. The following attempts by later scholars to reconsider his threefold taxonomy are significant to demonstrate \"Jakobson’s tripartition is not sufficient for discerning the cultural variety of translation processes, although it has provided its conceptual basis\" (Torop, 2008, p. 256). Given its revisited versions, intersemiotic translation may not necessarily be restricted to the translation of a verbal sign into non-verbal sign systems since the binary opposition between verbal and non-verbal signs has recently been problematized with multimedia forms. Although adaptations from literary works to multimodal texts such as film, music, opera, and theater are frequent, attempts to assess these activities within the context of intersemiotic translation might be regarded as a relatively recent area of study. Since this type of re-creation involves the transformation from a single language system into a text created by multimodal forms -light, stage design, choreography, actor/actress gestures, music- the translation logic suggests a different procedure. The purpose of this article is to argue that stage adaptations from literary works can be viewed as intersemiotic translations and the process is two-fold. The stage adaptation of the book Deli Kadın Hikayeleri (Mad Woman Tales) by Nok Tiyatro will be used as an example to demonstrate the transformation of linguistic signs into multimodality.
Keywords: Adaptation; multimodality; intersemiotic translation; stage adaptations; literary texts.